Depot risperidone-induced adverse metabolic alterations in female rats - Horska, Katerina; Ruda-Kucerova, Jana; Karpisek, Michal; Suchy, Pavel; Opatrilova, Radka; Kotolova, Hana (Journal of psychopharmacology (Oxford, England), 2017)
Atypical antipsychotics are associated with adverse metabolic effects including weight gain, increased adiposity, dyslipidaemia, alterations in glucose metabolism and insulin resistance. Increasing evidence suggests that metabolic dysregulation precedes weight gain development. The aim of this study was to evaluate alterations in adipokines, hormones and basic serum biochemical parameters induced by chronic treatment with depot risperidone at two doses (20 and 40 mg/kg) in female Sprague-Dawley rats. Dose-dependent metabolic alterations induced by risperidone after 6 weeks of treatment were revealed. Concomitant to weight gain and increased liver weight, an adverse lipid profile with an elevated triglyceride level was observed in the high exposure group, administered a 40 mg/kg dose repeatedly, while the low dose exposure group, administered a 20 mg/kg dose, developed weight gain without alterations in the lipid profile and adipokine levels. An initial peak in leptin serum level after the higher dose was observed in the absence of weight gain. This finding may indicate that the metabolic alterations observed in this study are not consequent to body weight gain. Taken together, these data may support the primary effects of atypical antipsychotics on peripheral tissues.
Keywords: Animals; Female; antipsychotika; hmotnostní přírůstek; Antipsychotic Agents; ženské pohlaví; Weight Gain; lipidy; Leptin; Lipids; Adipokines; risperidon; Rats, Sprague-Dawley; Risperidone; Sprague−Dawley rats; leptin; potkani Sprague-Dawley; depot risperidone; Adipokine; krysa rodu Rattus; zvířata; lipid profile; Rats; adipokiny